SPECTROPHOTOMETRIC ESTIMATION OF NITRO TYROSINE BY AZO - COUPLING REACTION - GOPI A,; ANUSHREE,; DEVARAJU KS, (International Journal of Pharma and Bio Sciences, 2014)
3-Nitrotyrosine has been identified using techniques like immunohistochemistry, HPLC, GCMS to demonstrate as a relevant biomarker in various disorders such as neurological, cardiovascular and others. Estimation of 3-NT by spectrophotometric method has been performed to measure 3-NT over decades. However none of the above methods have been translated to diagnose the diseases, but pathological conditions. Therefore here is an attempt to develop a method to be employed as a diagnostic tool. Current work is focussed on including preparation of 3-NT and further to derivatives using β-Napthol to yield diazotised product. All these intermediates of diazotized products have been characterized by ESI MS and the final colored dye was measured spectrophotometrically which exhibits λ max at 551 nm. The dye has been measured and compared with the direct measurement of 3-NT. The sensitivity of measurement of 3-NT increases by 10 fold, by and large we can estimate 20 µM concentration of 3-NT.